KONSEP DASAR HIPERGRAF DAN SIFAT-SIFATNYA - Faiq Fauziya Putri; Triyani Triyani; Ari Wardayani (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
This article discusses fundamental properties of hypergraphs. Hypergraphs are generalization of graph which hyperedges, edges in hypergraph, can join more than two vertices. The fundamental properties in this article are the vertices degrees, connection in hypergraphs, and dual hypergraph. connectivity in hypergraphs in this article are walks, trails, strict trails, path, and cycles. In the end of this article, we present a few examples of problems that can be represented by hypergraph.